Synthesis of Spirooxoindole Derivatives (JOURNAL OF ADVANCES IN CHEMISTRY, 2014)
This review summarizes the methods for preparing spirocyclic oxoindole derivatives in the past years until 2012 which are divided into several groups according to ring size of the fused spiroindoles.